Inhibition Efficiency of Extracts from Leaves of Piper betle Linn., Piper Sarmentosum Roxb., and Andrographis Paniculata (Burm.f.) Nees on the Growth of Colletotrichum Gloeosporioides in Nam Dok Mai Mango (Mongifera indica Linn.) (Journal of Namibian Studies : History Politics Culture, 2023)
The efficiency of betal leaf, wildbetal leafbush and kariyat extract for funyal inhibition of Colletotrichum gloeosporioides on Nam Dok Mai Mango was studied. The objective was to study the herbs that are suitable for inhibition of Colletotrichum gloeosporioides that cause Anthracnose disease on Nam Dok Mai Mango and the appropriate concentration to extend the shelf life of Nam Dok Mai Mango. Three concentrations of three herbs extracted were used at 10, 15 and 20 ppm. The lowest concentrations were tested for Anthracnose disease inhibition and shelf life of Nam Dok Mai Mango by Dilution Susceptibility Test, using concentration at 10, 15 and 20 ppm. Measure the growth of hyphol on day 7 in PDA. Antifungal efficacy Showed that betal leaf extract was 0.00±0.00 mm. in all 3 concentrations, the wildbetal leafbush and kariyat extract were 3.23±0.25, 0.67±0.29, 0.40±0.17, 6.17±0.29, 6.00±0.50 and 5.00±0.50 mm. respectively. Betal leaf can inhibit furgal 100 percent at all concentration insignificantly. The lowest concentration was 10 ppm. can inhibit fungal growth on Nam Dok Mai Mango 100 and 96 percent compared with Nam Dok Mai Mango without soaked and soaked with distilled water respectively.